Urinary trans-anti-7,8,9,10-tetrahydroxy-7,8,9,10-tetrahydrobenzo(a)pyrene as the most relevant biomarker for assessing carcinogenic polycyclic aromatic hydrocarbons exposure - Barbeau, Damien; Lutier, Simon; Choisnard, Luc; Marques, Marie; Persoons, Renaud; Maitre, Anne (Environment international, 2018)
Polycyclic aromatic hydrocarbons (PAH) are ubiquitous pollutants present as complex mixtures in the environment. Among them, benzo(a)pyrene (BaP) is classified as carcinogenic to humans by the International Agency of Research on Cancer. Taking into account all absorption ways, human biomonitoring allows PAH exposure assessment, but biomarkers both specific to carcinogenic effect and sufficiently sensitive are lacking. In this work, we proposed the urinary 7,8,9,10-tetrahydroxy-7,8,9,10-tetrahydrobenzo(a)pyrene (7,8,9,10-OHBaP) stemming from hydrolysis of BaP-7,8-diol-9,10-epoxide, the ultimate carcinogenic BaP metabolite, as biomarker of PAH exposure. A simple and highly sensitive analytical method, with a limit of quantification (LQ) reaching 0.06pmol/L (0.02ng/L), was described and validated. The relevance of urinary 7,8,9,10-OHBaP concentrations adjustment by creatinine was demonstrated. In a group of 24 non-occupationally PAH exposed subjects, only 15% of 7,8,9,10-OHBaP levels was below the LQ and the last daily void has been found as the best sampling time. Tobacco consumption had a significant positive effect on 7,8,9,10-OHBaP concentrations with a 90e percentile equal to 0.05nmole/mole creatinine (nmol/mol) and 0.03nmol/mol for smokers and non-smokers, respectively. In case of occupational PAH exposure, all the pre- and post-shift urinary 7,8,9,10-OHBaP levels of 7 non-smoking workers in a prebaked electrodes production plant were above the LQ. Concentrations ranged from 0.05 to 0.91nmol/mol and accumulation of 7,8,9,10-OHBaP into organism of workers during the working week was clearly observed. The best sampling time was the post-shift at the end of week but samples should also be collected at pre-shift the beginning of week to assess the background level. Finally, the urinary 7,8,9,10-OHBaP elimination kinetic through the weekend was studied using non-linear mixed effect modelling. Mean apparent urinary half-life was 31.5h with low inter-individual variability. Describing key characteristics of urinary 7,8,9,10-OHBaP as PAH exposure biomarker, this work should promote its use for future large-scale biomonitoring campaigns. [Display omitted] •7,8,9,10-Tetrahydroxy-7,8,9,10-tetrahydrobenzo(a)pyrene as biomarker of exposure•Description and validation of simple and highly sensitive analytical method•Samples should be collected in the evening and at the end of the working week.•90e percentile was 0.05nmole/mole creatinine for smokers and 0.03 for non-smokers.•Urinary elimination half-life was 31,5h with low inter-individual variability.